A high‐gain miniaturized half‐mode substrate integrated waveguide leaky wave antenna with integrated phase inverter. Issue 12 (7th September 2022) - Duan, Rui; Zhang, Bing; Zhou, Yanping; Huang, Kama
Abstract: A leaky wave antenna (LWA) based on half‐mode substrate integrated waveguide (HMSIW) is presented. Integrated phase inverters are used to eliminate the far‐field cancelation from the adjacent radiating element with half‐wave spacing. The ground plane is extended to reflect the quasi‐magnetic‐dipole radiation pattern from the backfire to the boresight for enhanced antenna gain. Two linear arrays with differential feeding are deployed back‐to‐back along their longitude, by which the far‐field radiation adds constructively that leads to further increased antenna gain. The proposed antenna features shorter electric length compared with counterparts of the same gain. Agreement is achieved between simulation and measurement. The proposed antenna has a measured impedance bandwidth of 11–12.8 GHz (15.6%), the measured maximum gain of 16.2 dBi @ 11.6 GHz. The antenna's beam scans from 20° to 50° in the boresight with the input signal's the frequency. By using the phase inverter, the extended ground plane and the back‐to‐back deployment, the proposed antenna produces equal gain with shorter antenna's electric length.